2001
DOI: 10.7863/jum.2001.20.8.877
|View full text |Cite
|
Sign up to set email alerts
|

Sonohysterography for the diagnosis of residual trophoblastic tissue.

Abstract: Sonohysterography for detection and diagnosis of residual trophoblastic tissue is an accurate and safe procedure. Further studies comparing the efficacy of sonohysterography with that of diagnostic hysteroscopy are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…On SHG submucous fibroids were broad based, hypoechoic, well defined solid masses with shadowing and an overlying layer of echogenic endometrium that disorts the endometrial myometrial interface. This is comparable with the results in the study conducted by Patricia C Davis et al (6) Residual trophoblastic tissue was detected in a patient with post partum bleeding which did not respond to repeated D &Cs.SHG showed a heterogenous mass attached to emdometrial lining which correlated with study conducted by Zalel Y.et al (7) and Wolman et al (8) The major drawback of the study was that no case of endometrial carcinoma could be detected. This was probably due to the fact that only a few patients in the postmenopausal age group were included in the study.…”
Section: Focal Endometrial Lesionssupporting
confidence: 82%
“…On SHG submucous fibroids were broad based, hypoechoic, well defined solid masses with shadowing and an overlying layer of echogenic endometrium that disorts the endometrial myometrial interface. This is comparable with the results in the study conducted by Patricia C Davis et al (6) Residual trophoblastic tissue was detected in a patient with post partum bleeding which did not respond to repeated D &Cs.SHG showed a heterogenous mass attached to emdometrial lining which correlated with study conducted by Zalel Y.et al (7) and Wolman et al (8) The major drawback of the study was that no case of endometrial carcinoma could be detected. This was probably due to the fact that only a few patients in the postmenopausal age group were included in the study.…”
Section: Focal Endometrial Lesionssupporting
confidence: 82%
“…10À14 In a previous study, we evaluated the use of sonohysterography for the diagnosis of residual trophoblastic tissue before undertaking operative hysteroscopy 5 ; we found that the lesion's continued adherence to the uterine wall after introduction of fluid into the uterus was highly suggestive of residual trophoblastic tissue. However, it was still unknown whether the demonstration of blood flow within such lesions would enhance diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…5 Briefly, after the vagina and cervix were cleansed with antiseptic (Polydin solution [P.V.P.-Iodine 10%]; Fischer Pharmaceuticals, Tel-Aviv, Israel), an 8F Foley catheter with a 3-ml balloon and a plastic guide was introduced transcervically into the uterine cavity using sterile long forceps. Once the balloon was in the proper position (ie, in the cervical os), it was slowly filled with 1À2 ml of sterile saline solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These procedures, however, require general anesthesia and are associated with risks (anesthesia-and procedure-related complications and endometrial adhesions) as well as considerable inconvenience for the patients. 1,5,6 Recently, transvaginal sonohysterography with removal of retained tissue under vision has gained popularity [7][8][9][10] because the ability of a regular sonographic examination to accurately detect retained products of conception has been questioned. [11][12][13] Thus, physicians caring for symptomatic patients who have undergone D&E have to rely on their clinical judgment supplemented by the limited diagnostic capabilities of the sonographic examination to decide between a surgical procedure and continuation of conservative treatment.…”
mentioning
confidence: 99%